Pengaruh Metode Pembelajaran Menggunakan Papan Luncur dan Pullbuoy terhadap Kecepatan Renang Gaya Crawl 25 Meter Club (ACC) Semarang - PUTRA, PRASTITIS YUDHARMANTO; Supriyono, Supriyono (Indonesian Journal for Physical Education and Sport, 2023)
The purpose of this study was to determine the effect of the learning method using skateboards and pullbuoys on the speed of 25m crawl style swimming in Abdul Aquatic Course Semarang students. As well as the difference and which is better between a skateboard and a pullbuoy. The data analysis technique in this study used inferential statistical analysis, hypothesis testing. The results showed that the R-square value of the learning method using the pull buoy was greater than the exercise using a skateboard. It means, "training using a pull buoy is better to use in increasing the speed of swimming in the 25-meter crawl style for the students of Club Abdul Aquatic Course (AAC) Semarang". The conclusion is that the exercise using a pullbuoy is better than a skateboard in increasing the speed of swimming in the 25-meter crawl style of students at the Abdul Aquatic Course Semarang club. The advice obtained by the researcher is that the trainer is expected to be able to use exercises using pullbuoys as a form of training program at a crawl speed swimming style of 25 meters.